CELEBRATING FLORES DE MAYO: AN IN-DEPTH LOOK AT THE CULTURE AND TRADITION IN BRGY. DANCALAN, DONSOL, SORSOGON. - Gilbert E. Lopez (Journal of English Education and Linguistics, 2023)
In the Philippines, Flores de Mayo is a well-known religious and cultural celebration that typically takes place in the month of May. The culmination of the month-long celebration is the Santacruzan procession, also referred to as the "Queen of May" pageant. The goal of this research is to give readers a thorough understanding of Flores de Mayo in Brgy. Donsol, Sorsogon, and Dancalan. In order to collect information from the local population and important informants, the study used qualitative research techniques like interviews and observations. Members of the community with knowledge and expertise with Flores de Mayo made up the study's participants. The study's findings demonstrated the significance of Flores de Mayo in Brgy culture and tradition. Dancalan. Many religious and cultural customs are observed during the event, including the recitation of prayers, the giving of flowers, and the participation of young girls in the Santacruzan procession. The survey also discovered that over time, Flores de Mayo celebrations have changed as new customs and practices have been added. For instance, the festival now includes a street dancing competition, which is a well-liked occasion in the neighbourhood. This study sheds light on Flores de Mayo's cultural and religious significance in Brgy. Donsol, Sorsogon, and Dancalan. The festival, which has changed over time to incorporate new customs and practices, is a significant aspect of the culture and heritage of the neighborhood. The study emphasizes the value of protecting and fostering local communities' cultural heritage